Benefits of combined interventions for cognitive enhancement in older adults - Angela Maria Sacramento; Henrique Salmazo da Silva; Gislane Ferreira de Melo; Grasielle Silveira Tavares Pulin; José Neander Silva Abreu; Isabelle Patriciá Freitas Soares Chariglione (Brazilian Society of Geriatrics and Gerontology, 2022)
Objective: To investigate the effects of different combined interventions (Stimullus, MEMO, physical activity, and psychoeducation) on the cognitive performance of older adults. Methods: This is a quasi-experimental study with pre- and post-intervention. Thirty-four older adults underwent different combined interventions for a period of 48 weeks and were evaluated at three different points (pre-intervention; post-cognitive intervention; post-physical activity or psychoeducation intervention). Cognitive domains (verbal episodic memory, executive function, general cognitive performance) and depressive symptoms were evaluated. Results: Postintervention gains in global, attentional, and mnemonic cognition were observed, as well as a reduction in depressive symptoms. The MEMO intervention + physical activity or psychoeducation resulted in greater cognitive gains, while Stimullus + psychoeducation showed benefits only in evocation and the free learning index, while Stimullus + physical activity resulted in improvement in the investigated variables. Conclusion: The results of these combined interventions appear promising for healthy older adults and the impact of these interventions should be discussed with individual older patients and evaluated more broadly in the context of public health.